THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL ATTITUDE AND LOCUS OF CONTROL ON FINANCIAL BEHAVIOR ON EMPLOYEES AT MNC FINANCE MEDAN - Devi Ziwiana Nainggolan; Rina Bukit; Chairul Muluk (CV. Radja Publika, 2024)
The aim of this research is to analyze Financial Behavior among employees at MNC Finance Medan, such as Financial Literacy, Financial Attitude and Locus of Control. The population is all employees of MNC Finance Medan. For this research, the population, as sample, consisted of 150 people. Primary data collection was carried out using a questionnaire measured by Likert scale. Secondary data was obtained from direct observation and books related to this research. The results of the data research show that Financial Literacy, Financial Attitude and Locus of Control simultaneously, have a positive and significant effect on the Financial Behavior of employees at MNC Finance Medan. Through testing the coefficient of determination (R2), the value R=0.795 was obtained, which means that there is a close relationship between Financial Literacy, Financial Attitude and Locus of Control on Financial Behavior among employees at MNC Finance Medan, namely 79.5%. Strengthened by the partial significance test results, it is stated that Financial Literacy, Financial Attitude and Locus of Control have a positive and significant effect on Financial Behavior among the employees at MNC Finance Medan.